PUBLIC RELATIONS STRATEGY IN SCHOOL IMAGE EFFORTS AT INTEGRATED ELEMENTARY SCHOOL - Sholihah, Ika Maziyyatus; Sapuding, Baiyinah; Hefniy, Hefniy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Improving the school's image must be connected to the participation of the community, which is an essential factor in supporting the achievement of programs held in educational institutions. In addition, implementing Public Relations management in educational institutions becomes a communication link or an extension of information that will be conveyed to the public. This study describes the Public Relations strategy in building the school's image to become a superior school. This research was conducted at An-Nadwa Integrated Elementary School. This study uses a descriptive qualitative approach, and in collecting data, researchers use interview techniques, observation and documentation studies. The main subjects in this study are Public Relations, school principals, teachers and students. Researcher results show; the Public Relations Strategy of communication and cooperation between parents of students or the community and educational institutions. Furthermore, Build a School Image to become a preeminent educational institution